2010
DOI: 10.4111/kju.2010.51.4.233
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Factors for Patients with pT1a Renal Cell Carcinoma

Abstract: PurposeAlthough the prognosis of patients with pT1a stage renal cell carcinoma (RCC) is generally good, some of these patients show distant metastasis. In this study, we intended to identify the perioperative and pathologic prognostic factors for patients with pT1a stage RCC.Materials and MethodsA total of 93 patients who were diagnosed with pT1aN0M0 RCC between January 1995 and December 2004 were included. All the patients underwent radical (n=63, 67.7%) or partial (n=30, 32.3%) nephrectomy by a single surgeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…In the present study, five of 133 patients with pT1aN0M0 RCC (3.8%) experienced tumor recurrence (median follow-up time, 57.8 months). In previous studies, the 5-year RFS rates were 88–93% in patients with pT1aN0M0 RCC ( 5 , 6 ). The 5-year RFS rate in our study was higher than that in the previous studies.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…In the present study, five of 133 patients with pT1aN0M0 RCC (3.8%) experienced tumor recurrence (median follow-up time, 57.8 months). In previous studies, the 5-year RFS rates were 88–93% in patients with pT1aN0M0 RCC ( 5 , 6 ). The 5-year RFS rate in our study was higher than that in the previous studies.…”
Section: Discussionmentioning
confidence: 91%
“…By contrast, there were no patients with bone recurrence in the present study. Kim et al reported that the lungs were the major site of recurrence in patients with pT1aN0M0RCC (four of nine patients), and only one patient had a recurrence in the bone ( 5 ). Therefore, it remains controversial whether the bone is a preferred site of recurrence in pT1aN0M0 RCC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations